(untitled) (European Journal of Pure and Applied Mathematics, 2019)
Decisions on the choice of varieties to be planted in a region are delicate because they can have positive or negative long-term consequences on the economic, environmental and nutritional level of a country.Â For this reason, a multi-criteria decision making (MCDM) based approach is proposed to conduct this choosing process. The proposed approach first of all makes it possible to identify alternatives, i.e. agricultural varieties, criteria with their weighting and evaluation process, in interaction with the stakeholders in the production-processing-consumption food chain. Afterward, PROMETHEE method (I and II) is used to aggregate the preference informations stemming from the structuring process and make it possible to choose the best agricultural varieties suitable for a given region. An Application for the selection of suitable cowpea varieties for the Central-Eastern region of Burkina Faso is made to demonstrate the implementation and effectiveness of our approach. As a result, the varieties KVx442-3-25SH (Komcallé) and Yiis-Yandé emerged as the best choices of suitable cowpea varieties for the Central-Eastern region of Burkina Faso